A Beasty story - Martin, Bill, 1916-2004.; Kellogg, Steven (San Diego : Silver Whistle/Harcourt Brace, 1999)
A group of mice venture into a dark, dark woods where they find a dark brown house with a dark red stair leading past other dark colors to a spooky surprise.
BR
Accelerated Reader AR
Keywords: Mice -- Fiction; Color -- Fiction; Stories in rhyme